2015
DOI: 10.1002/asna.201412184
|View full text |Cite
|
Sign up to set email alerts
|

Planet formation in post‐common‐envelope binaries

Abstract: To understand the evolution of planetary systems, it is important to investigate planets in highly evolved stellar systems, and to explore the implications of their observed properties with respect to potential formation scenarios. Observations suggest the presence of giant planets in post-common-envelope binaries (PCEBs). A particularly well-studied system with planetary masses of 1.7 MJ and 7.0 MJ is NN Ser. We show here that a pure first-generation scenario where the planets form before the common envelope … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4
2

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…A hybrid scenario may be also possible, with accretion of the ejected gas onto already existing planets. Several studies have been car-ried out on this matter and some authors favor one scenario over the other (see e.g., Völschow et al 2014;Schleicher & Dreizler 2014;Bear & Soker 2014;Schleicher et al 2015). In any case, these scenarios must take into account that ∼90% of the PCEBs, as found by Zorotovic & Schreiber (2013), have observed apparent period variations, implying that the hypothetical planets are very good at surviving the PCEB formation process and/or the common envelope material is very efficient in forming planets.…”
Section: Introductionmentioning
confidence: 99%
“…A hybrid scenario may be also possible, with accretion of the ejected gas onto already existing planets. Several studies have been car-ried out on this matter and some authors favor one scenario over the other (see e.g., Völschow et al 2014;Schleicher & Dreizler 2014;Bear & Soker 2014;Schleicher et al 2015). In any case, these scenarios must take into account that ∼90% of the PCEBs, as found by Zorotovic & Schreiber (2013), have observed apparent period variations, implying that the hypothetical planets are very good at surviving the PCEB formation process and/or the common envelope material is very efficient in forming planets.…”
Section: Introductionmentioning
confidence: 99%
“…The latter correspond to massive giant planets of several Jupiter masses on planetary orbits of a few AU. It has been suggested that at least some of these planets may have a second-generation origin (Völschow et al 2014;Schleicher & Dreizler 2014;Bear & Soker 2014;Schleicher et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Schleicher & Dreizler (2014) studied 12 PCEBs, elaborating on NN Ser. A recent summary of the question on whether the planets are first-generation planets, i.e., were formed with the stellar binary system, or second generation planets (e.g, Völschow et al 2014), i.e., formed in the post-CE phase from a circumbinary disk, is given by Bear & Soker (2014) and Schleicher et al (2015). We note that PCEBs are only one possible formation route to RPNs…”
Section: Real Planetary Nebula (Rpn) Formationmentioning
confidence: 90%